PENERAPAN MEDIA BONEKA TANGAN BERBANTUAN METODE MAKE A MACTH UNTUK MENINGKATKAN KEMAMPUAN BERCERITA SISWA KELAS II SD STKIP MUHAMMADIYAH BANGKA BELITUNG - Ali Sodikin; Asyraf Suryadin; Sasih Karnita Arafatun (Jurnal Inovasi Penelitian, 2020)
The problem of this research was the presence of the students who are shy when telling stories in front of the class, and the student’s lack in involvement during the learning process. From the number of 28 students in a class there are 18 students whose the skills in telling the story are poor. This research was carried out to find out whether there was an increasingof the student’s ability in tellingthe stories on story telling materials in grade II of STKIP Muhammadiyah Elementary School. This research is quantitative type, with the method "Quasi Experimental design" (Nonequivalent Nontrol Group Design) which is tested on two groups, namely group A as the experimental class and group B as the control class. The sample used was purposive sampling where the sample taken from 56 students, with the techniques of collecting the data using assessment instruments to tell stories and fable stories. This study uses sample related t-test (polled variant) for data analysis techniques. The learning process uses hand puppets media assisted with the make a match method. The results of analysis the data in this study showed that the average value of the experimental class students was 71,607 and the average value of the control class students was 70,750 after treatment using the related sample polled (polled variant) t-test percentage level of the ttable = 0, 05 obtained the results of hypothesis testing that is with the value of tcount = 2.330 ≥ value of ttable = 2, 048 then Ha accepted. This showed that there is an increasingof the student’s ability to telling the story of grade II students of SD STKIP Muhammadiyah Bangka Belitung on storytellingmaterial using hand puppet media assisted by the make a macth method